The territorial contours of terrorism: a conceptual model of territory for non-state violence - Pinos, Jaume Castan (Terrorism and political violence, 2020)
Our article challenges a common discourse that terrorist groups are relatively disinterested in territory by exploring emerging theories about territory and territoriality. We use these theories to introduce a new conceptual model of the importance of territory for terrorism that contrasts a group’s Sovereignty Claims over Territory (SCOT), which corresponds with the ultimate territorial aims of the group, with its Effective Control of Territory (ECOT), which relates to the ability of an organization to exert influence over a particular territory. Contrasting these dimensions of territory allows us to develop several archetypes of territorially-motivated terrorism. Our model predicts that, in contrast to common deterritorial discourses, truly non-territorial terrorism is likely to be quite rare as most groups engaged in violence have territorial ambitions in one way or another. We then use our model to interrogate the salience of territory to three representative cases: the Islamic State, ETA, and FARC-EP. Our analysis shows that territory remains a central motivating factor for these groups as their overall territorial aims tend to remain constant whereas their ability to control territory is more susceptible to change. We conclude by discussing the implications of our model and analysis for future research.